The parish in wartime (Woodbridge, Suffolk)
xiii, 601 sayfa, [2] sayfa harita
Keywords: “In the early twentieth century the Church of England remained a significant institution in the lives of the people of Oxfordshire. It was for many a key provider of education and social activities as well as being a focus for religious worship and community life. The two surveys in this volume show a range of aspects of the Church at work in the last unclouded summer before the Great War of 1914-18, and also detail the responses of both clergy and people to four years of conflict. The returns to the bishop by clergymen in each parish reveal the opportunities as well as the struggles that the war brought to many households and the ways in which the conflict proved to be a catalyst for social and religious change. The reports are presented here in full with biographical notes on the clergy and an extensive introduction.“ --